Media Pembelajaran Augmented Reality untuk Meningkatkan Kemampuan Spasial Matematis pada Konsep Geometri - Yanuarto, Wanda Nugroho; Iqbal, Agung Muhammad (Edumatica : Jurnal Pendidikan Matematika, 2022)
This study aims to develop an augmented reality (AR) learning media to improve the mathematical spatial ability of junior high school in geometry material. The method used in this study is a research and development method by following the steps of level 3 development. In this study, the product developed was augmented reality learning media. Data collection techniques are unstructured interviews, questionnaires and tests with information sources from mathematics education lecturers, two junior high school teachers as material validators and informatics engineering lecturers as media validators. The data analysis technique in this study used descriptive qualitative analysis. The research instrument used a learning outcomes questionnaire, geometry learning outcomes test, and documentation. The results showed that the development of augmented reality as a learning medium can be used to have a positive influence on the effectiveness of lessons in the classroom. But on the other hand, the weakness of augmented reality media is that students must use a minimum Android-based smartphone device and have a camera in it. The study results obtained are to produce AR learning media that can improve mathematical spatial abilities.